Empowering Diversity Through Transformational Leadership: A Pathway to Inclusive Excellence - Ardi Ardi; Yohana FCP Meilani; Andrianto Iskandar; Priscillia Chandra; Jessica (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
This study examines the pivotal role of transformational leadership in fostering diversity and inclusion within organizations. The research offers a comprehensive understanding of how transformational leadership can enhance organizational outcomes by investigating the interrelationships between inclusive leadership, synergy diversity climate, relational coordination, organizational identification, task performance, and leader-directed helping behavior. This study collected and analyzed relevant academic articles, case studies, and theoretical papers published in reputable journals using a systematic literature review approach. This methodology allowed for a comprehensive examination of existing research and knowledge gaps. By synthesizing these findings, the study provides a deeper understanding of how transformational leadership can empower diverse teams and contribute to inclusive excellence. Findings reveal that transformational leadership positively influences relational coordination and organizational identification, and improved task performance. Inclusive leadership practices and supportive leader behaviors create a more cohesive and engaged workforce, ultimately contributing to organizational success. This study underscores the importance of transformational leadership in leveraging diversity to achieve inclusive excellence and provides practical guidance for leaders seeking to cultivate inclusive cultures.